If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-2d/5+3=9
We move all terms to the left:
4-2d/5+3-(9)=0
We add all the numbers together, and all the variables
-2d/5-2=0
We multiply all the terms by the denominator
-2d-2*5=0
We add all the numbers together, and all the variables
-2d-10=0
We move all terms containing d to the left, all other terms to the right
-2d=10
d=10/-2
d=-5
| 105=-31.75n+1.75n^2 | | 37(n-1)=4 | | 3/5(b-7)=1 | | C=15n+84 | | (3x+17)+(1/2x+5)=180 | | 2x^2-16x=4x^2-3x-7 | | 36-12x=12x-36 | | 3+5(x+4)=47 | | X+9/2=2x-7 | | 9c-10=6+c | | 2x+20=5x | | 2/3+3m/2=25/6 | | 8x-(3x+9)=1 | | 9j=-12 | | X-4√x=32 | | 3/5x=11/2 | | 8=4(r-17) | | (3x-2)*7=133 | | 5+−2m+6=11 | | 11−2x=5x−3 | | 6y-2y-1=7 | | 3(2x)=6 | | -4.9t^2+12t-7.35=0 | | 12-5h=h+8 | | 3s-11=s+9 | | -3(t+5)=(4t+2)=8 | | 3(8-6x)=30 | | 3(2)x=6 | | 6x=2x+50 | | 14p-7p=7 | | 30x+200=1100 | | 25+3x=5.5x |